(untitled) (Journal of history, 2017)
Main conceptual positions and methodological paradigms to problem contemporary political and social anthropology of the "nomadic statehood" are considered in the article. There are considered different approaches and methods of the study of the shaping and operating the political system "nomadic statehood". Debate and conflicting conclusions of modern historical science reflect the level of theoretical and methodological approaches and show lack of logical tools for understanding the essence and nature of social and political change in nomadic societies. Research evidence shows that it is necessary to take into account the problem of succession, analogies and special features of the state in the imperial tradition of the Imperial confederations. The article deals with diversified approaches to the problems by adding the migratory habits of political entities of their systematization and reconstruction of a complex set of different types and models of power coupled into a single imperial structure.